An Exploration on Parent’s Gendered Perception - Pokharel, Samidha Dhungel (Tribhuvan University Journal, 2019)
Perception refers to the social knowledge which influences person’s attitudes and behavior. Though the process of perception is similar, it differs from person to person depending upon the context. Based on the survey study conducted on Kathmandu Metropolitan city, this study explores the parental perception toward stereotypical thinking about sons and daughters. Furthermore, it also explores what factors in regards to religion, gender, ethnicity, education and income is more influential in shaping perception. The study was carried out during the year 2011 to 2013 with total of 269 respondents including father and mother having at least one son and daughter. Data were collected through a set of both structured and unstructured questions. Findings of the study suggest that stereotypical perception about boys and girls are deeply rooted in Nepalese society. Stereotypical perception toward boys is more rigid than girls. It has also been observed that perception is contextual and significantly influenced by gender, religion, ethnicity, education and economy. However educational status and economic condition are the major factors that influence shaping people’s perception mostly. It can be concluded that bringing change in stereotypical perception is possible through improving peoples’ educational status and income.